Production of Liquid Smoke From Bamboo Waste Using a Pyrolysis Reactor: Optimization and Kinetics Studies - Abrina Anggraini, Sinar Perbawani; Yuniningsih, Susy (Jurnal IPTEK, 2021)
There are many ways for preserving wood through the use of agricultural or biomass waste like bamboo. Its utilization can be used as a safe natural wood preservative for the community. In order to obtain a qualified liquid smoke and consumed-safe it is necessary to engineer the condenser conduit pipes. As a consequence, this study needs a performance test of condenser conduit pipe on pyrolysis reactor device. The purpose of this study is to determine the performance quality of pyrolysis reactor device based on the optimum of long condenser conduit pipe and to determine the reaction order. In this study, the pyrolysis process of 2,5 kgs bamboo was using a pyrolysis reactor in optimum operating conditions, conducted with condenser conduit pipes size 23 cm, 33 cm, 43 cm, 53 cm, 63 cm and 73 cm at temperature of 250ºC for 2 hours. The results of this study indicate that the optimal liquid smoke yield is obtained from 23 cm long condenser conduit pipe (21.66%); the mass of lost material is 52.49% found in 73 cm pipe; the performance of the pyrolysis reactor is 206.25 found in 23 cm pipe g/hour.m; and the reaction occured was included as the first order of reaction.